Communication networks in common-pool resource games: field experimental evidence (2015)
We explore the role of communication networks and message types on behavior in a common pool resource game. In an artefactual field experiment, we introduce two network structures allowing participants to transmit non-binding suggestions to the other players with whom they were connected. We study the effect of these networks on subjects’ payoffs. In a centralized network, “bad” (self-regarding) suggestions have a negative and permanent effect, whereas “good” (cooperative) suggestions have a null (or even negative) effect due to their limited credibility. In a decentralized network the positive effect of “good” suggestions is permanent (although smaller than in the centralized network), while “bad” suggestions have a more limited effect. Although allocation to positions in the network is exogenous, we find a positive correlation between network centrality and other-regarding behavior when transmitting “good” and “bad” messages.